2022
DOI: 10.3390/jcm11154509
|View full text |Cite
|
Sign up to set email alerts
|

PCOS Physiopathology and Vitamin D Deficiency: Biological Insights and Perspectives for Treatment

Abstract: Recent literature has stressed the importance of vitamin D (VD) in polycystic ovary syndrome (PCOS). Women with PCOS are deficient in VD, particularly those with a higher weight. Hypovitaminosis is a risk factor for glucose intolerance, and reduced levels of VD is associated with insulin resistance and increased diabetes risk. Since women with PCOS and hirsutism seem to have lower levels of VD than women with PCOS without hirsutism, a correlation between VD deficiency and hyperandrogenism may be suggested. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…Conditions associated with insulin resistance, such as obesity and diabetes mellitus, are often accompanied by increased adiposity or hyperglycemia [ 44 ]. Obesity and diabetes are independently associated with an altered female reproductive function [ 13 , 45 , 46 ]. Interestingly, a recent study reported that ELOVL5 is involved in embryonic development and lipid metabolism [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions associated with insulin resistance, such as obesity and diabetes mellitus, are often accompanied by increased adiposity or hyperglycemia [ 44 ]. Obesity and diabetes are independently associated with an altered female reproductive function [ 13 , 45 , 46 ]. Interestingly, a recent study reported that ELOVL5 is involved in embryonic development and lipid metabolism [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide studies in various cells, including granulosa cells from women with PCOS and non-PCOS controls, have revealed several potential genes and pathways, such as the ERK/MAPK and VEGF signaling pathways [ 6 , 11 ]. However, OHSS (and PCOS) has a complex etiology and genetic basis and the disease pathogenesis and mechanism still largely remain unclear [ 5 , 6 , 12 , 13 ]. In this study, we aimed to identify the potentially essential genes and pathways in PCOS patients who would be prone to developing OHSS and to identify potential markers that may be linked to the OHSS and its pathobiology using a transcriptomic approach.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, the prevalence of GDM is around five percent [ 19 ]. However, the prevalence is steadily increasing, as maternal obesity is a major predisposing factor for GDM, and more women of child-bearing age are overweight or obese [ 20 ]. The risks of GDM include an increased risk of large babies, caesarean sections, birth trauma, still births, and neonatal jaundice.…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
“…It is also thought to increase the risk of future type 2 diabetes. Apart from hyperglycemia, GDM is associated with increased oxidative stress and inflammation in the placenta and fetus [ 20 , 21 ]. GDM also increases trans-placental fatty acid and lipoprotein transport and turnover [ 22 , 23 ].…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation